Isolasi dan Uji kadar Senyawa Flavonoid Pada Daun Kelor (Moringa Oleifera) Menggunakan Metode Klt Dan Spektrofotometri Uv-Vis - Munawir; Sri Harmoni, Dewi Natalia; Maharani, B. Fitria (JURNAL KESEHATAN TROPIS INDONESIA, 2025)
Moringa leaves (Moringa oleifera) are a source of bioactive compounds, including flavonoids, which have therapeutic benefits such as antioxidants and anti-inflammatory. This research aims to isolate and identify flavonoids in Moringa leaves using Thin Layer Chromatography (TLC) and UV-Vis Spectrophotometry methods. Moringa leaf samples were extracted using 70% ethanol via the maceration method. The TLC test results showed an Rf value of 7.7, identical to quercetin as the main flavonoid. Quantitative analysis using UV-Vis spectrophotometry at a wavelength of 425 nm produced flavonoid levels of 0,99%. This discovery confirms the presence of quercetin in Moringa leaves, supporting its potential as a source of active compounds useful for pharmaceutical and health applications